Internet-based atlas of the primate spinal cord - Tokuno, H.; Tanaka, I.; Senoo, A.; Umitsu, Y.; Akazawa, T.; Nakamura, Y.; Watson, Charles (Elsevier, 2011)
In 2009, we reported an online brain atlas of the common marmoset (Callithrix jacchus) at http://marmoset-brain.org:2008. Here we report new digital images of the primate spinal cord sections added to the website. We prepared histological sections of every segment of the spinal cord of the common marmoset, rhesus monkey and Japanese monkey with various staining techniques. The sections were scanned with Carl Zeiss MIRAX SCAN at light microscopic resolution. Obtained digital data were processed and converted into multi-resolutionary images with Adobe Photoshop and Zoomify Design. These images of the primate spinal cords are now available on the web via the Internet.